Social Anxiety Levels among Adolescents at Social Child Welfare Institutions in Pekanbaru City - Adhara, Hajar; Erika, Erika; Wahyuni, Sri (Alta Dharma Publisher, 2023)
Background: Social anxiety is a fear of getting negative judgments from others when individuals are involved in certain social activities or situations. Social anxiety can also be experienced by teenagers who live in Social Child Welfare Institutions. Objective: This study aims to obtain an overview of the level of social anxiety in adolescents who live in Social Child Welfare Institutions in Pekanbaru City. Method: This quantitative study used a descriptive survey method, with a cluster random sampling technique of 240 adolescents as a sample. The research instrument is the Liebowitz Social Anxiety Scale questionnaire. Result: The results of this study indicate that 69.7% of the 240 adolescents living in Social Child Welfare Institutions experienced social anxiety. The dominating level is mild social anxiety (33.8%), followed by moderate social anxiety (21.3%), marked social anxiety (10%), severe social anxiety (3.8%), and very severe social anxiety (0.8%). The social situation that makes most respondents feel afraid or anxious is going to a party or event (74.2%), while the most avoidance response is urinating in a public toilet (55.2%). Conclusion: It can be concluded that adolescents living in Social Child Welfare Institutions experience social anxiety at various levels. Therefore, this research intends to make related institutions (Social Services) cooperate with Social Child Welfare Institutions to pay more attention to teenagers' development. Support can be in the form of providing facilities and health professionals who can help prevent social anxiety from escalating into a more severe condition or even causing other mental illnesses